Humble Authority: A Theological Study of Jesus' Leadership in the Gospel of John and Its Implications for Church Leadership Today - Oksje M.O. Rumagit; Soejono Soejono; Agus Suhariono (LPPM Universitas PGRI Sumatera Barat, 2023)
Leadership in the Christian context is often confronted with two seemingly contradictory concepts: authority and humility. This study aims to analyze the concept of servant leadership exemplified by Jesus Christ in the Gospel of John, focusing on how spiritual authority is manifested through service, sacrifice, and humility. Using a descriptive qualitative approach with in-depth literature review, this study explores Jesus' concept of leadership from the perspective of the Gospel of John and its relationship to the spirituality of service. The results show that true spiritual authority cannot be separated from humility and sincere service. It was found that self-denial opens space for the work of the Holy Spirit, which enables one to lead according to God's will. The study's conclusion emphasizes that leadership authority lies not in power or a particular position, but in total submission to God's will through self-denial and the example of Christ. This study provides practical implications for the development of servant leadership in the context of contemporary Christianity